2009
DOI: 10.1007/s00280-009-1078-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the exposure equivalence of oral versus intravenous temozolomide

Abstract: PurposeOral temozolomide is approved in many countries for malignant glioma and for melanoma in some countries outside the USA. This study evaluated the exposure equivalence and safety of temozolomide by intravenous infusion and oral administration.MethodsSubjects with primary central nervous system malignancies (excluding central nervous system lymphoma) received 200 mg/m2 of oral temozolomide on days 1, 2 and 5. On days 3 and 4, subjects received 150 mg/m2 temozolomide either as a 90-min intravenous infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…2B). This exceeds the concentration required to observe synergism in vitro and is >20-fold higher than plasma exposures observed in the clinic (32). Time-course experiments indicated that trapping increases for 2 hours and then reaches a plateau (Fig.…”
Section: Potentiation Of Alkylating Agents By Parp Inhibitors In Vitromentioning
confidence: 81%
See 1 more Smart Citation
“…2B). This exceeds the concentration required to observe synergism in vitro and is >20-fold higher than plasma exposures observed in the clinic (32). Time-course experiments indicated that trapping increases for 2 hours and then reaches a plateau (Fig.…”
Section: Potentiation Of Alkylating Agents By Parp Inhibitors In Vitromentioning
confidence: 81%
“…19). The high concentrations of TMZ required (>300 mmol/L) significantly exceed the maximum exposures observed in the clinic (32). This suggests that either clinically tolerated regimens containing PARP inhibitors and TMZ cannot engage the trapping mechanism or currently available assays are not sensitive enough to detect physiologically relevant levels of trapping.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, reversed-phase high-performance liquid chromatography (HPLC) with UV [10][11][12] or MS/MS [8,13] detection was used in the analysis of TMZ. Baker et al combined HPLC analysis with radioanalysis ( 14 C-TMZ was applied) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The half-life for MTIC was calculated to be 2.5 min [2,6] but has been determined to be 1.9 h [7,8] and 25 min [7,9] in human plasma in vivo and in vitro, respectively. AIC is stable in human plasma at room temperature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Temozolomide demonstrated activity against experimentally induced tumors in mice and rats [5,6]. Positron emission tomography (PET) scanning in patients showed that intravenous 11 C-labeled temozolomide readily crossed the blood-brain barrier and entered brain tissue [7]. A predictive pharmacokinetic model was developed by Gallo et al [2], because the direct measurement of drug concentrations in human tumors was found difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%